The history of the United States - Guelzo, Allen C.; The Teaching Company ([Chantilly, VA ] : The Teaching Company, 2003)
Presents lectures delivered by Professor Allen C. Guelzo concerning the history of the United States
Part 7. lecture 73. The civil rights movement ; lecture 74. The new frontier and the great society ; lecture 75. The rise of mass media ; lecture 76. The Vietnam war ; lecture 77. The women's movement ; lecture 78. Nixon and watergate ; lecture 79. Environmentalism ; lecture 80. Religion in Twentieth-century America ; lecture 81. Carter and the Reagon revolution ; lecture 82. The new world order ; lecture 83. Clinton's America and the Millnium ; lecture 84. Reflections
Title from title screen
Lecturer: Allen C. Guelzo
Keywords: United States -- History